John S. Stirling journal - Stirling, John S., active 1875.
Journal (1875 February 15-April 6) kept by Stirling on a voyage from New York, N.Y., to San Francisco, Calif., via Panama.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Voyages and travels; California -- Description and travel; New York (N.Y.) -- Description and travel; Panama -- Description and travel; San Francisco (Calif.) -- Description and travel